Missense variants in ANO4 cause sporadic encephalopathic or familial epilepsy with evidence for a dominant-negative effect - Yang, Fang; Begemann, Anais; Reichhart, Nadine; Haeckel, Akvile; Steindl, Katharina; Schellenberger, Eyk; Sturm, Ronja Fini; Barth, Magalie; Bassani, Sissy; Boonsawat, Paranchai; Courtin, Thomas; Delobel, Bruno; et al. (American Journal of Human Genetics, 2024)
Anoctamins are a family of Ca2+-activated proteins that may act as ion channels and/or phospholipid scramblases with limited understanding of function and disease association. Here, we identified five de novo and two inherited missense variants in ANO4 (alias TMEM16D) as a cause of fever-sensitive developmental and epileptic or epileptic encephalopathy (DEE/EE) and generalized epilepsy with febrile seizures plus (GEFS+) or temporal lobe epilepsy. In silico modeling of the ANO4 structure predicted that all identified variants lead to destabilization of the ANO4 structure. Four variants are localized close to the Ca2+ binding sites of ANO4, suggesting impaired protein function. Variant mapping to the protein topology suggests a preliminary genotype-phenotype correlation. Moreover, the observation of a heterozygous ANO4 deletion in a healthy individual suggests a dysfunctional protein as disease mechanism rather than haploinsufficiency. To test this hypothesis, we examined mutant ANO4 functional properties in a heterologous expression system by patch-clamp recordings, immunocytochemistry, and surface expression of annexin A5 as a measure of phosphatidylserine scramblase activity. All ANO4 variants showed severe loss of ion channel function and DEE/EE associated variants presented mild loss of surface expression due to impaired plasma membrane trafficking. Increased levels of Ca2+-independent annexin A5 at the cell surface suggested an increased apoptosis rate in DEE-mutant expressing cells, but no changes in Ca2+-dependent scramblase activity were observed. Co-transfection with ANO4 wild-type suggested a dominant-negative effect. In summary, we expand the genetic base for both encephalopathic sporadic and inherited fever-sensitive epilepsies and link germline variants in ANO4 to a hereditary disease.
CRIS-Team Scopus Importer:2024-06-07
Keywords: ANO4; anoctamin; Ca; developmental and epileptic encephalopathy; GEFS+; phospholipid scramblase; temporal lobe epilepsy; TMEM16D